Mobile Enabled Streaming System (International Journal of Engineering and Computer Science, 2017)
In this paper we present mobile enabled streaming system stream-me architecture which integrates local storage NAS, cloud storage and peer to peer storage. Our aim to provide users video contents on their mobile device at anywhere and at anytime. Keywords: Cloud Computing; Multimedia server; Multimedia Streaming; P2p Network.